More zeal than discretion : the westward adventures of Walter P. Lane - Bryan, Jimmy L. (Elma Dill Russell Spencer series in the West and Southwest ;, 2008)
"Walter P. Lane emigrated from Ireland as a young boy, fought in three wars, sailed the Texas coast with a privateer, and traveled to California and Arizona in search of gold. What drove this man, who in many ways typifies the adventurers who contributed to the westward expansion in the United States during the early nineteenth century? As Jimmy L. Bryan Jr. reveals in this superbly researched and nuanced work, Walter P. Lane, like many men of his generation, was driven in part by his ideals of gender, ethnicity, and nationality. In this first full-length biography of Lane, Bryan has exhaustively mined personal papers, memoirs, contemporary sources, and archived collections to produce a portrait, not only of an individual who exemplifies "the proud military tradition of Texas," but also of the times in which Lane lived and the principles that fired his imagination and stoked his ambition."--Jacket.